2015
DOI: 10.1089/ten.tea.2014.0070
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Potential of Juvenile and Adult Human Articular Chondrocytes for Cartilage Tissue Formation in Three-Dimensional Biomimetic Hydrogels

Abstract: Regeneration of human articular cartilage is inherently limited and extensive efforts have focused on engineering the cartilage tissue. Various cellular sources have been studied for cartilage tissue engineering including adult chondrocytes, and embryonic or adult stem cells. Juvenile chondrocytes (from donors below 13 years of age) have recently been reported to be a promising cell source for cartilage regeneration. Previous studies have compared the potential of adult and juvenile chondrocytes or adult and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…The manufacturer of DeNovo-Natural Tissue combined allograft particulated juvenile cartilage with fibrin adhesive to create a product that got regulatory approval as a minimally processed allograft in the United States [9,27]. As a cell source, DeNovo-Natural Tissue offers significant theoretical benefits with increased replicative and matrix synthetic ability compared with adult chondrocytes [1,22,38]. Similarly, other companies are producing minimally processed allograft tissue matrices.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer of DeNovo-Natural Tissue combined allograft particulated juvenile cartilage with fibrin adhesive to create a product that got regulatory approval as a minimally processed allograft in the United States [9,27]. As a cell source, DeNovo-Natural Tissue offers significant theoretical benefits with increased replicative and matrix synthetic ability compared with adult chondrocytes [1,22,38]. Similarly, other companies are producing minimally processed allograft tissue matrices.…”
Section: Discussionmentioning
confidence: 99%
“…However, harvesting human ESCs (HESCs) is surrounded by considerable ethical, moral and religious dilemmas and barriers. There is evidence that younger cells, such as chondrocytes, are a more promising cell source for cartilage regeneration (Smeriglio et al 2014).…”
Section: Embryonic and Young Stem Cellsmentioning
confidence: 99%
“…Complex organic matter mainly includes collagen and proteoglycan. Interstitial fluid contains mostly water, the flow of the fluid not only has an important influence on cartilage mechanical properties, also has a close relationship with the vascular tissue nutrient transport [1]. At the same time, articular cartilage has a very low coefficient of friction, which plays a good role in lubrication [2].…”
Section: Introductionmentioning
confidence: 99%
“…The following finite element analysis procedure is carried out within a time step 1 t  , supposing that 1 1 0 1s t t t     , time integral parameter 0.6   , each time step reflects the changing process of load at this moment, the relationship between stress and velocity was calculated, as shown in Fig.2 (b). The simulation results are compared with the results that used the penalty finite element method, and the experimental data obtained by the Spilker and Holmes et al in Rensselaer Polytechnic Institute [14], the contrast curves are shown in Fig.2 (b).…”
mentioning
confidence: 99%